THE UNIQUE OF SPEECH ACTS USED IN SONG LYRICS OF TAYLOR SWIFT IN THE THEME OF LIFE LESSONS - Gawa, Dila Maya Titian; Munir, Ahmad; Setiawan, Slamet (Universitas Putera Batam, 2023)
Illocutionary act is performed in saying something, and includes acts such as betting, promising, denying, stating, apologizing, threatening, predicting, ordering and requesting. This study aimed to analyze illocutionary act and function of illocutionary act in the three-song lyric of Taylor Swift that have the same theme, that is life lessons. After the data is being collected, the data is analyzed based on the theory of illocutionary act by Searle (1996) and function of illocutionary acts by Leech (1983). The study shows that there are four categories of illocutionary acts that found from the three songs of Taylor Swift. Those are representatives, directives, commissive and expressive. Representative act was found as the most dominant categories of illocutionary act with 67 data (70,52%), followed by directives with 16 data (16,84%), commissive with 10 data (10,52%) and expressive with 2 data (2,1%). Moreover, there are four types of function of illocutionary acts found in the song lyrics of Taylor Swift. There are Collaborative, conflictive, competitive and convivial. Collaborative was the most dominant function of illocutionary act with 16 data (69,56%) followed by conflictive with 5 data (21,73%), competitive with 1 data (4,34%) and convivial with 1 data (4,34%). Lastly, speech act used in ELT has some implication for the student’s skill.